2019
DOI: 10.1177/1559827619850489
|View full text |Cite
|
Sign up to set email alerts
|

Compendium of Health and Wellness Coaching: 2019 Addendum

Abstract: The 2019 Addendum, in conjunction with the original health and wellness coaching (HWC) Compendium, organizes HWC literature with the aim of assisting researchers while providing a resource for practitioners. The 2019 Addendum to the HWC Compendium extends the initial work by adding HWC-related literature published in the past 2 years. The 2019 Addendum divides articles retrieved into 8 categories, including a new miscellaneous section complementing categories examining HWC effects on cancer, cholesterol, diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 43 publications
0
61
0
1
Order By: Relevance
“…A more substantial and coherent personal vision of one's ideal future results from coaching (Mosteo et al, 2016). A wide variety of health outcomes also result from coaching, such as increased quality of life measures, decreased pain, health care utilization (Hackshaw et al, 2016), and potential behavior change (Frates et al, 2011) (Sforzo et al, 2019; Wolever et al, 2013). Nevertheless, the outcomes assessed reflect a narrow part of the spectrum of possible desired outcomes (Athanasopoulou & Dopson, 2018; Theeboom et al, 2014).…”
Section: What Are the Desired Outcomes Of Coaching?mentioning
confidence: 99%
“…A more substantial and coherent personal vision of one's ideal future results from coaching (Mosteo et al, 2016). A wide variety of health outcomes also result from coaching, such as increased quality of life measures, decreased pain, health care utilization (Hackshaw et al, 2016), and potential behavior change (Frates et al, 2011) (Sforzo et al, 2019; Wolever et al, 2013). Nevertheless, the outcomes assessed reflect a narrow part of the spectrum of possible desired outcomes (Athanasopoulou & Dopson, 2018; Theeboom et al, 2014).…”
Section: What Are the Desired Outcomes Of Coaching?mentioning
confidence: 99%
“…The need for research evaluating the effectiveness of HWC as a means of enabling lifestyle behaviour change has been widely recognised. For example, in 2017, Sforzo and colleagues reviewed and organised the available literature into a compendium which was updated in 2019 (Sforzo et al, 2018(Sforzo et al, , 2019. The summary of results indicated that HWC could be beneficial in many circumstances.…”
Section: Existing Literaturementioning
confidence: 99%
“…Positive psychology coaching uses a strengths-based approach to help physicians identify and achieve positive emotions, create meaningful relationships, increase engagement and purpose, and develop coping skills for personal and professional stressors, including communication, improving resilience, team building, and mindfulness [14,19,21,[24][25][26]. Health and wellness coaching, which integrates positive psychology and promotes healthy behavior change as a means of averting or mitigating chronic life style-related diseases, remains a relatively unexplored potential treatment for burnout and stress management [13,[27][28][29].…”
Section: Coaching and Positive Psychologymentioning
confidence: 99%